Coconstructing knowledge in english classes through talk-in-interaction sequences - Schaumloeffel, Moisés (Universidade do Vale do Rio dos Sinos, 2019)
The present research paper presents the process of coconstruction of knowledge which occurred in English classes as an additional language. Aiming to describe how knowledge is coconstructed in English classes, naturalistic data (data that would occur without the presence of the researcher) was used having its verbal features transcribed based on the conventions of Jefferson (1984), which have been adapted by Schnack, Pisoni, and Ostermann (2005). The data comprises classroom interactions recorded in audio and video in an English Institute located in the South region of Brazil and three groups took part in the research – a low intermediate class, an advanced class, and a conversation advanced class. The data was analyzed based on how the participants of the interaction maintain the intersubjectivity of the interaction through socially shared cognition (GARFINKEL, 1967; SCHEGLOFF, 1991), how participation occurs in sequences where coconstruction of knowledge is evidenced (GARCEZ, 2007; FRANK, GARCEZ, KANITZ, 2012), and the nature of the knowledge produced - reproductive or emergent knowledge. (CONCEIÇÃO 2008; GARCEZ, 2006; FRANK, GARCEZ, KANITZ, 2012). IRE sequences were also explored in order to establish a parameter of comparison with the interactional phenomena occurred in the moments where coconstruction of knowledge was present. (GARCEZ, 2006; MEHAN, 1979). Through the data analyzed, three main practices to achieve coconstruction of knowledge have been evidenced: firstly, the search for a shared cognition of a specific referent; secondly, the use of examples to construct a definition; and thirdly, the production of guessing based on assumptions.
Keywords: Coconstrução de conhecimento; Fala-em-interação; Sequência IRA; Interações de sala de aula; Análise da Conversa; Aulas de língua inglesa; Coconstruction of Knowledge; Talk-in-interaction; IRE Sequence; Classroom Interaction; Conversation Analysis.; English Classes